Forced oscillations of an infinite-dimensional oscillator under impulsive perturbations - Vlasenko, L. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Existence and uniqueness theorems for the impulsive differential operator equation d^2dt^2[Au(t)] + Bu(t) = f(t, u(t)) are obtained. The operator A is allowed to be noninvertible. The results are applied to differential algebraic equations and partial differential equations, which are not equations of Kovalevskaya type.